ANALISIS PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, DANA PIHAK KETIGA DAN KECUKUPAN MODAL TERHADAP PROFITABILITAS (ROA) PERBANKAN DI INDONESIA - Alan Oky Hermawan, 12.05.52.0097; Lisiantara, Anggana (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of credit risk, liquidity risk, deposits, and capital adequacy on profitability (ROA). Research was conducted on banks in Indonesia registered with Bank Indonesia and the Financial Services Authority.Â The sampling method in this study using purposive sampling method with a study period of 2012 through 2014. The data used in this study is data from the financial statements of banks that met the selection criteria. The analytical method used in this research is using Eviews using panel data. The research proves that the credit risk significant negative effect on ROA, while liquidity, third-party funds, and capital adequacy has no effect on ROA. Value Adjusted R Square is 0.143 it explain 14.3% variation of dependent can be explained by the independent variation, while the remaining 85.7% is explained by other variables outside the model.Keywords: Return On Asset, Loan to Deposit Ratio, Non-Performing Loans, Deposits, Capital Adequacy Ratio